Biaya Penyehatan Lingkungan pada Bidan Praktik Swasta di Kecamatan Gamping, Sleman, 2016 - Mohammad Mirza Fauzie (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Private midwives in conducting health services for public have potentiality to yield environmental pollution and disease transmission. To prevent those harms they should apply environmentalhealth efforts. This study was aimed to reveal those efforts through direct observation and interview about the expense. The observation consisted of: provision of clean water, managementof solid medical waste, control of insect rodent and annoying animals, and sterilization. The results identify that in clean water provision, the activities are: use water from local water company and water quality examination. In solid medical waste management: provide safety box astemporal disposal, and use chlorine to treat it, and cooperate with hospitals, community healthcenters and private companies to annihilate it. In insect, rodent and annoying animals control:the first act is using closed door to prevent, as well as gauze wires and traps; and insecticidesfor indoor control and keep house clean. In sterilization: room and utilities sterilization wih alcohol, chlorine and boiling/steaming technique. The average monthly expense for clean water isRp.62.272, for solid medical waste management: Rp.57.778, for insect, rodent and annoyinganimal control: Rp.41.041, and for sterilization: Rp.38.833. The average exense per month forthose four activities are Rp. 199.925. To keep the environmental health activities run, it needsupervision, monitoring and support from the local community health center and association ofmidwives, and SOP for each of the existing and planned effort should be developed.